Crystal structure of chlorido-4-fluorobenzyl-bis(2-methylquinolin-8-olato-κ2N,O)tin(IV), C27H22ClFN2O2Sn - Lee, See Mun *; Lo, Kong Mun *; Tiekink, Edward R. T. * (de Gruyter, 2019)
C27H22ClFN2O2Sn, tetragonal, P41 (no. 76), a = 9.38970(10) Å,c = 26.2753(4) Å, V = 2316.60(6) Å3, Z = 4, Rgt(F) = 0.0141,wRref(F2) = 0.0381, T = 293(2) K. CCDC no.: 1903610 The molecular structure is shown in the figure. Table 1 contains crystallographic data and Table 2 contains the list of the atoms including atomic coordinates and displacement parameters.